Lyssaviruses and the Fatal Encephalitic Disease Rabies - Scott, Terence Peter; Nel, Louis Hendrik (Frontiers in Immunology, 2021)
Lyssaviruses cause the disease rabies, which is a fatal encephalitic disease resulting in approximately 59,000 human deaths annually. The prototype species, rabies lyssavirus, is the most prevalent of all lyssaviruses and poses the greatest public health threat. In Africa, six confirmed and one putative species of lyssavirus have been identified. Rabies lyssavirus remains endemic throughout mainland Africa, where the domestic dog is the primary reservoir – resulting in the highest per capita death rate from rabies globally. Rabies is typically transmitted through the injection of virus-laden saliva through a bite or scratch from an infected animal. Due to the inhibition of specific immune responses by multifunctional viral proteins, the virus usually replicates at low levels in the muscle tissue and subsequently enters the peripheral nervous system at the neuromuscular junction. Pathogenic rabies lyssavirus strains inhibit innate immune signaling and induce cellular apoptosis as the virus progresses to the central nervous system and brain using viral protein facilitated retrograde axonal transport. Rabies manifests in two different forms - the encephalitic and the paralytic form - with differing clinical manifestations and survival times. Disease symptoms are thought to be due mitochondrial dysfunction, rather than neuronal apoptosis. While much is known about rabies, there remain many gaps in knowledge about the neuropathology of the disease. It should be emphasized however, that rabies is vaccine preventable and dog-mediated human rabies has been eliminated in various countries. The global elimination of dog-mediated human rabies in the foreseeable future is therefore an entirely feasible goal.